Estimates of cancer burden in Lombardy. Issue 3 (May 2013) - Gatta, Gemma; Ciampichini, Roberta; Bisanti, Luigi; Contiero, Paolo; Tessandori, Roberto; Baili, Paolo; Rossi, Silvia
Aims and background: Cancer registration in Lombardy covers almost half of the regional population and started in 1976 in the Varese province. The aim of this paper is to provide estimates of the incidence, mortality and prevalence of seven major cancers for the entire Lombardy region in the period 1970—2015. Methods: The estimates were obtained by applying the MIAMOD method, a statistical back-calculation approach to derive incidence and prevalence figures starting from mortality and relative survival data. Published data from the Italian cancer registries were modeled in order to estimate the regional cancer survival. Results: In Lombardy, about 9, 000 new cases of breast cancer, 8, 500 of colorectal cancer, 7, 200 of prostate cancer and 6, 700 of lung cancer were expected to be diagnosed in the year 2012. Incidence rates are still rising for female breast cancer, skin melanoma in both sexes, and lung cancer in women. By contrast, the rates have been declining for cervix and stomach cancer. For lung cancer in men, prostate cancer and colorectal cancer the rates increased, reaching a peak in different periods, and then decreased. Prevalence increased for all cancers considered except cervix cancer. The rise was less pronounced in stomach cancer due to the impressive reduction of its incidence and was striking for breast and prostate cancer, with 116, 000 and 58, 900 prevalent cases in 2012. Mortality dropped for all considered cancers with the only exception of lung cancer in women. Conclusion: This up-to-date picture of the cancer risk and burden in Lombardy shows the increasing demand for oncology services as one of the major challenges for the region. However, primary prevention is still the only way to simultaneously reduce incidence, prevalence and mortality rates, thus saving further lives and preserving health resources.